Impact of service quality dimensions on student satisfaction - Suroto, Suroto; Nurdyastuti, Tri (Manajemen dan Bisnis, 2023)
The purpose of this study was to examine the effect of service quality dimensions consisting of Tangibles, Reliability, Responsiveness, Assurance, and Empathy variables on student satisfaction at STIE AUB Surakarta. Respondents in this study were students at STIE AUB Surakarta. The analysis tool uses logistic regression. The sampling technique used is a random sampling technique. The consequences of the examination show that physical assets have a critical constructive outcome on fulfillment. Unwavering quality has a huge adverse consequence on understudy fulfillment. Responsiveness has a critical constructive outcome on understudy fulfillment. Confirmation has a huge beneficial outcome on fulfillment. Compassion has a huge beneficial outcome on fulfillment. The managerial implication of this result is that the management of STIE AUB Surakarta must increment the positive and huge factors that influence understudy fulfillment, namely the Tangibles, Responsiveness, Assurance, and Empathy variables, and reduce the variables that have a negative and significant effect, namely the Reliability variable so that the credibility of STIE AUB remains awake.